Hubungan Health Locus of Control dengan Kepatuhan Minum Obat pada Lansia Hipertensi di Wilayah Puskesmas Lerep Ungaran - Indarti Indarti; Iwan Ardian; Nutrisia Nu'im Haiya (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the relationship from resilience also qualities of life among breast cancer clients undergoing chemotherapy at Sultan Agung Islamic Hospital, Semarang. A quantitative cross-sectional design was included to 67 patients selected from accidental sample. Resilience was measured by Connor–Davidson Resilience Scale, while qualities of life was assessed using by EORTC QLQ-C30 instrument. Univariate analysis demonstrated that most patients exhibited moderate levels of resilience and quality of life. Bivariate analysis using Somers’ d revealed a strong and statistically significant also positive association from resilience then qualities of life (r = 0.629; p = 0.001). These shows indicate the higher resilience is consistently associated with better multidimensional quality of life during chemotherapy. The answers supporting the theoretical proposition that resilience functions as a central adaptive resource that modulates psychological distress, social functioning, and perceived health status. This study highlights the importance of integrating resilience-oriented psychosocial interventions into routine oncology care. Strengthening resilience is therefore essential not only for improving subjective well-being but also for optimizing comprehensive treatment outcomes in breast cancer clients undergoing long-term chemotherapy.